Faktor-Faktor Yang Mempengaruhi Keputusan Siswa SMK TJP Tuban Jurusan TKJ Untuk Melanjutkan Berwirausaha - Rika Dwi Safitri; Yosia Dian Purnama Windrayadi (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2026)
This study aims to determine the influence of income, self-esteem, opportunities, family environment, community environment, and personality factors on the decision of students majoring in TKJ at SMK TJP Tuban to continue entrepreneurship, both partially and simultaneously, and to determine which factors are most dominant in influencing students' entrepreneurial decisions. This study uses a quantitative approach with multiple linear regression methods. The population in this study were all 250 students majoring in TKJ at SMK Tuban, with a sample of 154 respondents determined using the Slovin formula. Data collection techniques were carried out through questionnaires using a Likert scale distributed online via Google Form. The data were analyzed using validity tests, reliability tests, descriptive analysis, normality tests, heteroscedasticity tests, t-tests, F-tests, and coefficients of determination with the help of SPSS 23. The results of the study indicate that partially the factors of income, self-esteem, opportunities, family environment, community environment, and personality have a significant influence on the decisions of students majoring in TKJ at SMK TJP Tuban. Simultaneously, these six variables also significantly influence the entrepreneurial decisions of eleventh grade students at SMK TJP Tuban. The entrepreneurial decision variable has the highest average score, which indicates that students are ready and have a strong desire to become entrepreneurs after graduation